Language Policy in Current Times - J.Prabhakara Rao (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
language policy earlier has been designed to promote languages in education, administration, and Judiciary, etc. It is seen as a powerful political instrument for promoting co-existence of different languages. Now effective technological and scientific (language) tools are available for formulation comprehensive language policies and their implementation. UNESCO is doing commendable work in this regard by tracking a number of capacity building initiatives to strengthen nations and their institution to faster the implementation of language policies. A comprehensive language policy aimed at language promotion should be framed up taking into account specificities of the linguistic and cultural diversity of the nation and the issue arose out of such diversity. This can be done by sharing and exchange of good practices with other nations. The language policy should highlight the need for extensively using technology for promoting and protecting languages, developing e-content and supporting e-governance in native languages etc. The language policy should also make a detailed analysis of native languages for contribution economy of the nation for sustainable development and inclusive growth.